2016
DOI: 10.1177/0271678x15611136
|View full text |Cite
|
Sign up to set email alerts
|

Direct voxel-based comparisons between grey matter shrinkage and glucose hypometabolism in chronic alcoholism

Abstract: Alcoholism is associated with widespread brain structural abnormalities affecting mainly the frontocerebellar and the Papez's circuits. Brain glucose metabolism has received limited attention, and few studies used regions of interest approach and showed reduced global brain metabolism predominantly in the frontal and parietal lobes. Even though these studies have examined the relationship between grey matter shrinkage and hypometabolism, none has performed a direct voxel-by-voxel comparison between the degrees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…Brain volume deficits in this sample of chronic alcoholics reflected those observed in the full group of alcoholics from which this sample was selected (Pfefferbaum et al 2018;Sullivan et al 2018) and are consistent with reports from previous imaging studies (Cardenas et al 2007;Ritz et al 2016){Makris et al 2008}. Using atlas-based quantitative MRI, this study demonstrated that the alcoholics examined herein had volume deficits in frontal, cingulate, insular, parietal, and hippocampal regions as observed in the larger sample from which this group was drawn (Sullivan et al 2018){Pfefferbaum 2018}.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Brain volume deficits in this sample of chronic alcoholics reflected those observed in the full group of alcoholics from which this sample was selected (Pfefferbaum et al 2018;Sullivan et al 2018) and are consistent with reports from previous imaging studies (Cardenas et al 2007;Ritz et al 2016){Makris et al 2008}. Using atlas-based quantitative MRI, this study demonstrated that the alcoholics examined herein had volume deficits in frontal, cingulate, insular, parietal, and hippocampal regions as observed in the larger sample from which this group was drawn (Sullivan et al 2018){Pfefferbaum 2018}.…”
Section: Discussionsupporting
confidence: 86%
“…Two imaging studies lent further evidence of frontal lobe involvement in alcoholism. A positron emission tomography (PET) study provided a direct voxel-by-voxel comparison between the degrees of structural and metabolic abnormalities in 17 alcoholics and identified gray matter shrinkage in nodes of the frontostriatal, frontocerebellar, and frontolimbic circuits, including frontal and cerebellar cortices, cingulate gyrus, thalamus, and hippocampus (Ritz et al 2016). A longitudinal structural MRI study on 222 individuals with alcohol dependence reported frontal regional volumes that were most extensively affected, including the precentral, supplementary motor, and medial cortices (Sullivan et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Neuroradiologically, the mainstay of studies of uncomplicated alcoholism concurs with neuropathological findings, especially of white matter involvement . Quantitative MRI studies report tissue shrinkage typically in the anterior superior vermis, involving lobules I‐V with additional sites of volume deficit in the white matter of the cerebellar hemispheres (; for review,), also exacerbated by common alcoholism‐related concomitant complications …”
Section: Introductionmentioning
confidence: 90%
“…While disagreements between structural and functional neuroimaging methods exist [85,86], structural and functional neuroimaging results are associated [87][88][89][90][91]. Despite some negative findings [92][93][94][95], lower thalamic grey matter volumes in drug-dependent individuals, across drugs of abuse including alcohol, cocaine, nicotine, methamphetamine, opioids, cannabis and synthetic cannabinoids [95][96][97][98][99][100][101][102][103][104][105][106][107], have been reported. Such decreased grey matter volume in the thalamus (as well as the amygdala and cortical regions including the PFC) is associated, for example, with increased craving for methamphetamine [102], more lifetime tobacco use [108], more years of substance use in polysubstance users [109], and shorter abstinence length in alcohol users [110].…”
Section: (A) Structural and Functional Integrity Of The Thalamus In Amentioning
confidence: 99%